Protective and coping behaviour of representatives of socionomic professions with different professional experience - L. M. Popova (Publishing House of the State University of Management, 2021)
The results of a theoretical and empirical study of psychological defenses and coping strategies of behaviour among employees of social service institutions are presented. The following methods were used in diagnostic procedures: “Life style Index” (R. Plutchik, G. Kellerman) and “Methods of coping behavior” (R. Lazarus and S. Folkman). As a result of the study, the respondents revealed the intensity of psychological defenses of the type “intellectualization”, “reactive education”, “denial” and coping strategies “problem solving planning”, “positive reassessment” and “search for social support”. The correlations of psychological defenses and coping strategies of respondents are interpreted. The specific differences of protective-coping behaviour among employees with different professional experience are shown: employees with up to ten years of experience are more inclined to compensated behaviour, and employees with ten years of experience or more – to self-control, a rational approach to solving difficulties, a responsible attitude to what is happening. The results of the study may be useful in the placement of personnel, in career counseling, in the framework of discourses on professional psychology. And further study of psychological defenses and coping strategies will help to understand the specifics of the professional identity of employees of a socionomic profile.